Penerapan Eksperimen (Balon Mengembang tanpa Ditiup) dalam Meningkatkan Pemahaman Siswa pada Pembelajaran IPA Kelas 5 MI Malik Ibrahim - Lina Agustin; Muhammad Suwignyo Prayogo; Nurmala Karima; Nanda Riski Istikomah (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This study aims to apply a simple experimental approach titled “Balloon Expands Without Being Blown” to enhance fifth-grade students’ understanding of gas concepts in science learning at MI Malik Ibrahim. The study originates from the observation that students often struggle to grasp the concepts of gases and acid–base reactions, which are typically taught in a purely theoretical manner without engaging hands-on experiences. The research employed a Classroom Action Research (CAR) design following Kurt Lewin’s model, which includes four interconnected stages: planning, acting, observing, and reflecting. The participants consisted of 22 fifth-grade students from MI Malik Ibrahim. The findings reveal a substantial improvement in both learning achievement and classroom participation after the experimental activity was introduced. Students’ average scores increased from 62 to 85, with 82% showing measurable progress. Furthermore, inquiry and discussion activities became more frequent, and most students could correctly explain the formation of carbon dioxide (CO₂) gas. Overall, the results suggest that the balloon expands without being blown experiment effectively fosters scientific conceptual understanding, promotes active engagement, and stimulates motivation toward learning science.